Food security of Ukraine: national and global level - Melnyk, Tatyana; Tunitska, Yuliia; Banas, Dmytro (Economics and Business Review, 2023)
The aim of this paper is to examine the level of food security in Ukraine in comparison to global regions and European countries in the context of the COVID-19 pandemic and the Russian-Ukrainian war. For this purpose a variety of indicators were examined including population dynamics, food balance, FAO indicators and the Global Food Security Index. The results show that in spite of its agricultural potential Ukraine is behind the global and European indicators of food security with the exception of fish products. Barriers to achieving high levels of food security include incomplete legislative reforms, inadequate funding, infrastructure deficiencies, corruption and non-compliance with standards. International cooperation and improved national and regional strategies are needed to overcome the consequences of the war.